Pola Pikir Masyarakat dan Kinerja Kepala Desa: Mengapa Visi Hebat dalam Perencanaan Pembangunan Sering Kali Terhambat Oleh Kondisi Budaya Lokal - Alexander H. Badjuka; Edis Adelia Dunggio; Arit Pratama Putra Lihawa; Yulita Yulita; Ruaida Kadir (Perspektif Administrasi Publik dan hukum, 2026)
This study examines how community mindset and local cultural conditions influence the performance of village heads in implementing development planning in Libungo Village, Suwawa District, Bone Bolango Regency. The research applies a qualitative descriptive approach through in-depth interviews, field observations, and documentation studies. The main informants consisted of the village head, village officials, and members of the local community. The findings reveal that development implementation in Libungo Village remains constrained by both structural and cultural factors. Damaged roads, disconnected bridges caused by floods, and limited public participation indicate that development has not yet achieved optimal results. The village head emphasized that low human resource capacity and a dependency mentality among residents are major obstacles in realizing development programs. Many residents prefer to maintain their status as social assistance recipients rather than actively participate in empowerment programs and village development initiatives. This condition is reinforced by local cultural patterns such as passive attitudes, patron-client relations, and resistance to change. The study concludes that the success of village development is not solely determined by the competence and vision of the village head, but also by the readiness of community mindset and local culture to support social transformation. Therefore, participatory approaches, community empowerment, and long-term mindset transformation are necessary to strengthen sustainable village development.